Umbilical cord-mesenchymal stem cells induce a memory phenotype in CD4+ T cells - Sengun, Ezgi; Wolfs, Tim G. A. M.; van Bruggen, Valéry L. E.; van Cranenbroek, Bram; Simonetti, Elles R.; Ophelders, Daan; de Jonge, Marien I.; Joosten, Irma; van der Molen, Renate G. (Frontiers in Immunology, 2023)
Inflammation is a physiological state where immune cells evoke a response against detrimental insults. Finding a safe and effective treatment for inflammation associated diseases has been a challenge. In this regard, human mesenchymal stem cells (hMSC), exert immunomodulatory effects and have regenerative capacity making it a promising therapeutic option for resolution of acute and chronic inflammation. T cells play a critical role in inflammation and depending on their phenotype, they can stimulate or suppress inflammatory responses. However, the regulatory effects of hMSC on T cells and the underlying mechanisms are not fully elucidated. Most studies focused on activation, proliferation, and differentiation of T cells. Here, we further investigated memory formation and responsiveness of CD4+ T cells and their dynamics by immune-profiling and cytokine secretion analysis. Umbilical cord mesenchymal stem cells (UC-MSC) were co-cultured with either αCD3/CD28 beads, activated peripheral blood mononuclear cells (PBMC) or magnetically sorted CD4+ T cells. The mechanism of immune modulation of UC-MSC were investigated by comparing different modes of action; transwell, direct cell-cell contact, addition of UC-MSC conditioned medium or blockade of paracrine factor production by UC-MSC. We observed a differential effect of UC-MSC on CD4+ T cell activation and proliferation using PBMC or purified CD4+ T cell co-cultures. UC-MSC skewed the effector memory T cells into a central memory phenotype in both co-culture conditions. This effect on central memory formation was reversible, since UC-MSC primed central memory cells were still responsive against a second encounter with the same stimuli. The presence of both cell-cell contacts and paracrine factors were necessary for the most pronounced immunomodulatory effect of UC-MSC on T cells. UC-MSC derived IL-6 and TGFβ were shown to be important mediators for the immunomodulatory function. Collectively, our data show that UC-MSCs clearly affect T cell activation, proliferation and maturation, depending on co-culture conditions for which both cell-cell contact and paracrine factors are needed.